1983
DOI: 10.1021/i200021a024
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of nitrogen monoxide into aqueous potassium permanganate/sodium hydroxide and sodium sulfite/iron(II) sulfate solutions

Abstract: An experimental study on the absorption of low concentration nitrogen monoxide into aqueous KMnO,/NaOH and Na,SO,/FeSO, solutions has been conducted with two types of absorbers, a stirred tank and a bubble chamber. The absorption rates under various experimental conditions were measured. In the case of NO absorption into KMnO,/NaOH solutions, the rate is proportional to both the interfacial concentration of NO and either that of a complex formed in the solution or that of KMnO, depending on the pH values of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…In the reaction of ONOO - with MnO 4 - , both homolysis products, NO • and O 2 •- , are rapidly consumed by the detection reagent. The rate constant we obtained for the reaction of NO • with MnO 4 - , (3.5 ± 0.7) × 10 6 M -1 s -1 , is in excellent agreement with previously reported values of 3.93 × 10 6 , 1.18 × 10 6 , and 5.60 × 10 6 M -1 s -1 . For the reaction of O 2 •- with MnO 4 - , we determined a rate constant of (5.7 ± 0.9) × 10 5 M -1 s -1 at pH 11.7, which is lower than the earlier published value of (9.5 ± 0.8) × 10 5 M -1 s -1 at pH 9.4, but the discrepancy may be ascribed to the difference in pH.…”
Section: Discussionsupporting
confidence: 91%
“…In the reaction of ONOO - with MnO 4 - , both homolysis products, NO • and O 2 •- , are rapidly consumed by the detection reagent. The rate constant we obtained for the reaction of NO • with MnO 4 - , (3.5 ± 0.7) × 10 6 M -1 s -1 , is in excellent agreement with previously reported values of 3.93 × 10 6 , 1.18 × 10 6 , and 5.60 × 10 6 M -1 s -1 . For the reaction of O 2 •- with MnO 4 - , we determined a rate constant of (5.7 ± 0.9) × 10 5 M -1 s -1 at pH 11.7, which is lower than the earlier published value of (9.5 ± 0.8) × 10 5 M -1 s -1 at pH 9.4, but the discrepancy may be ascribed to the difference in pH.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent withSada et al. 's (1977) andUchida et al's (1983) results.Figure 8shows the measurements of NO absorption rate into a solution with 0.01 mol/L Downloaded by [University of Western Ontario] at 19:/L NaOH over a range of NO concentrations for various operating temperatures. The observed absorption rate decreases with the decreasing temperature from 50°C to 25°C Although the solubility of gases in liquid would increase as temperature decreases, however, the diffusivity of gases in liquid and reaction rate constants would decrease.…”
supporting
confidence: 93%
“…Although Uchida et al (1983) did the similar experiment with lower concentration of NO ranged from 399 to 1790 ppm, the study was still performed under 30 °C . They found that the reaction under low concentration of NO was first-order with respect to NO and first-order with respect to KMnO 4 , which was the same as the case with high NO concentration done by Sada et al (1977).…”
Section: Introductionmentioning
confidence: 99%
“…If the hydroxide concentration of the absorption solution is decreased, reaction (2) and the following reactions will take place in parallel [4]:…”
Section: Resultsmentioning
confidence: 99%
“…The absorption of NO in aqueous solutions of KMn04 and NaOH was investigated in the late 70's and early 80's by Teramoto et al [2], Sada et al [3] and Uchida et al [4]. The absorption experiments were performed in a semi-batchstirred vessel with a plane gas-liquid interface.…”
Section: Introductionmentioning
confidence: 99%